Chronic moderate alcohol consumption relieves high‐fat high‐cholesterol diet‐induced liver fibrosis in a rat model. (25th July 2018) - Sun, Furong; Zhuang, Zhenjie; Zhang, Dai; Chen, Yushuai; Liu, Shu; Gao, Nan; Shi, Junping; Wang, Bingyuan
Summary: Nonalcoholic fatty liver disease is a worldwide health issue and chronic alcohol consumption may have different effects on this disease. This study explored the role of chronic moderate alcohol consumption on high‐fat high‐cholesterol (HFHC) diet‐induced liver fibrosis in a rodent model. Male Sprague–Dawley rats were divided into five groups: standard chow group, standard chow plus Er Guo Tou (EGT, a Chinese spirit made from fermented cereals) group, HFHC group, HFHC plus EGT group, and HFHC plus pure ethanol (EtOH) group. Rats were fed standard chow or HFHC chow for 12 weeks. EGT or pure ethanol was administrated at a daily dose of 4 g/kg body weight via intra‐gastric gavage from week 4. At the end of week 12, hematoxylin and eosin staining, Sirius red and immunohistochemistry of liver sections were examined. The hepatic expression of F4/80, TNF‐α, IL‐1β, IL‐6, CXCL1, CXCL2, α‐SMA, Collagen, TGF‐β, MMP2, MMP9, and TIMP1 was calculated. Both moderate EGT and pure ethanol did not increase plasma endotoxin in the portal vein comparing with the FHFC group. EGT and pure ethanol did not improve hepatic inflammation, but ameliorated liver fibrosis in histology. Moderate EGT and pure ethanol ameliorated HFHC diet‐induced activation of Kupffer cells and hepatic stellate cells. In conclusion, chronic moderate EGT and pure ethanol could ameliorate HFHC diet‐induced liver fibrosis.